Distance education in physical education during COVID-19 quarantine in Ukraine - Kuznetsov, Andriy; Doroshenko, Veronika; Chernovsky, Sergey; Kramarenko, Alla; Malona, Svitlana; Rybalko, Petro (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
One of the major tasks of the social program of the state is to strengthen and maintain the health of youth. In the context of significant deterioration of the psychophysical readiness of young students, the issue of maintaining their health cannot be considered outside the context of physical education, which is of great social importance in this perspective. Moreover, the quality of higher education is equated with the quality of training of able-bodied professionals. This is ensured by the proper state of their health. In the period of quarantine, the students were forced to spend maximum time only on mental activity via distance mode of learning. An adequate and only possible response to the challenges of today is the use of distance learning technologies for students to effectively implement their physical education in quarantine. At the same time, one of the key problems is the proper organization of physical culture and health activities of students to maintain their health in conditions of extremely limited physical activity.